2019
DOI: 10.1016/j.shaw.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Metals in Shooting Ranges: A Biomonitoring Study

Abstract: BackgroundLead (Pb) exposure in shooting ranges has been reduced by various measures such as jacketed ammunition and lead-free primers. Nevertheless, this may lead to exposure to other metals, potentially resulting in adverse health effects.MethodsIn a cross-sectional study, 35 subjects from seven different shooting ranges were studied: four shooting instructors, 10 police officers, 15 Special Forces, and six maintenance staff members. Metals and metalloids were determined in blood and urine by inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
2
4
0
Order By: Relevance
“…Although most element concentrations did not differ significantly between both groups, the subjects of the high-exposure group had significantly higher concentrations of Sb in urine and Pb in blood samples compared to the control group. 31 Similar to the Belgian study, the high-exposure group in the present study showed higher BLL, still within the specified normal range. In a study by Hiller and Drexler, Pb and Sb concentrations in the blood and Sb concentrations in the urine of Bavarian police officers were examined.…”
Section: Focus On Metal Levelssupporting
confidence: 88%
See 1 more Smart Citation
“…Although most element concentrations did not differ significantly between both groups, the subjects of the high-exposure group had significantly higher concentrations of Sb in urine and Pb in blood samples compared to the control group. 31 Similar to the Belgian study, the high-exposure group in the present study showed higher BLL, still within the specified normal range. In a study by Hiller and Drexler, Pb and Sb concentrations in the blood and Sb concentrations in the urine of Bavarian police officers were examined.…”
Section: Focus On Metal Levelssupporting
confidence: 88%
“…One group was highly exposed to gunshot emissions and included (shooting instructors, special forces and shooting range maintenance staff); the other group served as a control group and was composed of police officers working at the administration. Although most element concentrations did not differ significantly between both groups, the subjects of the high‐exposure group had significantly higher concentrations of Sb in urine and Pb in blood samples compared to the control group 31 . Similar to the Belgian study, the high‐exposure group in the present study showed higher BLL, still within the specified normal range.…”
Section: Discussionsupporting
confidence: 75%
“…Although few studies have looked at biomarkers of exposure in firing range instructors, a study from Belgium did find that lead was elevated in blood and urine of firing range employees, including instructors, compared to a control group [ 25 ]. Other occupations where exposure to heavy metals is common may also provide insight into the biological response to firing emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have looked at biomarkers of exposure in ring range instructors, a study from Belgium did nd that lead was elevated in blood and urine of ring range employees, including instructors, compared to a control group (25). Other occupations where exposure to heavy metals is common may also provide insight into the biological response to ring emissions.…”
Section: Introductionmentioning
confidence: 99%